2001
DOI: 10.1046/j.0141-6707.2000.00297.x
|View full text |Cite
|
Sign up to set email alerts
|

Drought mortality of bush elephants in Hwange National Park, Zimbabwe

Abstract: African bush elephants inhabiting the undeveloped Kalahari Sands region of Hwange National Park, Zimbabwe are subject to episodic mortality during droughts.We monitored the drought-related mortality of elephants in Hwange National Park over the course of an extended drought between 1993 and 1995. The drought-related mortality of elephants was higher during 1994 than 1995, despite signi¢cantly higher rainfall in 1994 than 1995. We found signi¢cant di¡erences in the age-speci¢c mortality of elephants during 1994… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(101 citation statements)
references
References 11 publications
1
100
0
Order By: Relevance
“…African elephants, for example, have carcasses that are easily visible from the air for several years after death (DouglasHamilton and Hillman, 1981), and while carcasses have been used to inform local mortality rates (e.g. Dudley et al, 2001;Dunham, 2008) and CITES status (e.g. Wittemyer et al, 2013), we found no peerreviewed study exploiting the spatial location of carcasses.…”
Section: Introductionmentioning
confidence: 46%
“…African elephants, for example, have carcasses that are easily visible from the air for several years after death (DouglasHamilton and Hillman, 1981), and while carcasses have been used to inform local mortality rates (e.g. Dudley et al, 2001;Dunham, 2008) and CITES status (e.g. Wittemyer et al, 2013), we found no peerreviewed study exploiting the spatial location of carcasses.…”
Section: Introductionmentioning
confidence: 46%
“…Corfield, 1973;Walker et al, 1987;Dudley et al, 2001), disease (Berry, 1993;Lindeque, 1988;Turnbull et al, 1991), and predation also affect survival. Lions target unweaned calves in the Hwange National Park, Zimbabwe (Loveridge et al, 2006), and 4-to 15-year-old elephants in the Savuti Region of Botswana (Joubert, 2006).…”
Section: Deathsmentioning
confidence: 99%
“…These are usually expressed as high survival rates (Laws, 1969;Hanks, 1979;Whitehouse & Hall-Martin, 2000;Dudley et al, 2001;Moss, 2001;Wittemyer et al, 2005b;Gough & Kerley, 2006). Age-and sexspecific survival values have been published for several populations (table 3).…”
Section: Deathsmentioning
confidence: 99%
“…Smit and Grant (2009) mention induced mortality through starvation that can be caused by degradation of the top herbaceous layer as a result of such overuse. Oguto et al (2010) and Dudley et al (2001) also stated that such high densities of animals in one area may promote the spread of disease and other density dependent affects, resulting in increased mortality. Territorial fights between individuals as a result of such density dependent stress may also be responsible for increased mortality according to Mtahiko et al (2006).…”
Section: Location Of Water Points Visited By Different Speciesmentioning
confidence: 99%